Quality inventories on the operation and results of European Works Councils (Bologna, 2005)
"This publication presents the results of a research project on the functioning of European Works Councils (EWCs). In view of the revision of the EC Directive 94/95/EC the European Trade Union Confederation (ETUC) saw the need for a qualitative inventory on the operation of EWCs and the results that these new workers’ representative bodies had so far led to. The project that, therefore, was focused on analysing the ‘inner life’ of the EWCs was based on a qualitative and comparative case study analysis. The project was intended to provide indications for the improvement of effectiveness and efficiency of EWCs’ work. Furthermore, the project was aimed at analysing the role of EWCs with regard to the Europeanisation of industrial relations, on the one hand, and the impact of EWCs on national industrial relations, on the other. The project that was coordinated by the Fondazione Istituto per il Lavoro, Bologna, was carried out between November 2001 and March 2003."